International diet quality index and revised diet quality index relationship with type 2 diabetes disease: a case-control study - El-Sehrawy, Amr Ali Mohamed Abdelgawwad; Mukhlif, Bilal AbdulMajeed; Oghenemaro, Enwa Felix; Rekha, M. M.; Kumawat, Rohit; Sharma, Shilpa; Kumar, M. Ravi; Shalaby, Nagat Salah; Abosaoda, Munthar Kadhim; Kadhim, Abed J. (Frontiers in Nutrition, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a global health crisis linked to increased cardiovascular risk. Research indicates that better dietary quality—higher intake of fruits, vegetables, and whole grains, and lower intake of processed foods—reduces T2DM risk. This study examines the relationship between T2DM and dietary quality indices (DQI-I and DQI-R) to determine if adherence can lower diabetes risk. By analyzing dietary patterns in individuals with and without diabetes, the research aims to identify key nutritional factors influencing disease risk and provide evidence-based dietary recommendations for prevention and management.MethodsThis case-control study involved 128 T2DM patients and 256 controls, assessing dietary intake with a validated 168-item food frequency questionnaire to calculate the Dietary Quality Index-I (DQI-I) and Dietary Quality Index-R (DQI-R). Multivariable logistic regression analysis explored the relationship between DQI-I, DQI-R, and their components with T2DM development odds.ResultsThe mean (SD) age and body mass index (BMI) of participants, comprising 53.7% men, were 37.8 (7.8) years and 27.7 (3.3) kg/m2, respectively. In the final model, each standard deviation increase in the DQI-I score was associated with reduced odds of T2DM (odds ratio [OR] = 0.61; 95% confidence interval [CI] = 0.37–0.92; p = 0.046). Among the components of the DQI-I, a high adequacy score was significantly correlated with lower odds of T2DM (OR = 0.13; 95% CI = 0.05–0.36; p < 0.001). Additionally, participants in the highest tertile of the DQI-R score exhibited lower odds of T2DM compared to those in the lowest tertile (OR = 0.29; 95% CI = 0.11–0.49; p < 0.001). Furthermore, within the components of the DQI-R, a high moderation score was associated with a decreased risk of T2DM (OR = 0.19; 95% CI = 0.09–0.45; p < 0.001).ConclusionThe case-control study suggests a potential protective effect of diets with higher scores on the Diet Quality Index-International (DQI-I) and Revised Diet Quality Index (DQI-R) in reducing T2DM risk. Future research should focus on larger sample sizes and prospective designs to further investigate the DQI-I, DQI-R, and their components in relation to T2DM and other chronic diseases.